Comparative Outcomes of Flexible Ureterorenoscopy (FURS) versus Mini Percutaneous Nephrolithotomy (Mini PCNL) for Management of Large Proximal Ureteric Stones - Abbas, Muhammad Tahir; Rauf, Abdul; Khan, Fazal Ur Rehman; Usman, Rida; Fateh, Umer; Iftikhar, Sana (Biological and Clinical Sciences Research Journal, 2025)
Large proximal ureteric stones present a considerable management challenge, particularly in regions with high urolithiasis prevalence, such as Pakistan. With advancements in endourological techniques, both Flexible Ureterorenoscopy (FURS) and Mini Percutaneous Nephrolithotomy (Mini PCNL) have emerged as standard minimally invasive modalities; however, comparative evidence within the local population remains limited. Objective: To compare the stone-free rate, operative duration, hospital stay, and postoperative complications between Mini PCNL and FURS in the management of large proximal ureteric stones. Methods: A randomized controlled trial was conducted at the Department of Urology, National Institute of Kidney Diseases, Shaikh Zayed Medical Complex, Lahore, from June 2025 to September 2025. A total of 110 patients aged 18–65 years with large proximal ureteric stones (>1.5 cm) were enrolled through consecutive sampling and randomized into two equal groups: Mini PCNL (n = 55) and FURS (n = 55). All procedures were performed under general anesthesia by experienced consultants following standardized surgical protocols. Patients were followed for 4 weeks postoperatively, and stone-free status was assessed using CT KUB. Secondary outcomes included operative time, hospital stay, and complications based on the Clavien Dindo classification. Data were analyzed using SPSS 26.0, applying chi-square and independent t tests with significance set at p < 0.05. Results: The Mini PCNL group achieved a significantly higher stone-free rate (90.9%) compared to the FURS group (76.4%; p = 0.041). Mean operative time was shorter with Mini PCNL (49.6 ± 8.5 minutes) than with FURS (72.4 ± 11.3 minutes; p < 0.001). Conversely, hospital stay was significantly longer in the Mini PCNL group (3.4 ± 0.9 days) versus the FURS group (1.8 ± 0.6 days; p < 0.001). Postoperative complications were comparable between groups, with 16.4% in each group, and no statistically significant difference was observed (p = 1.000). Conclusion: Mini PCNL demonstrates superior stone-free rates and shorter operative times compared to FURS for large proximal ureteric stones, although it requires longer hospitalization. Both procedures exhibit comparable safety profiles. Mini PCNL may therefore be considered the more effective option in appropriately selected patients within the Pakistani population.